Agomelatine for Depression in Parkinson Disease: Additional Effect on Sleep and Motor Dysfunction. Issue 6 (December 2015) - Avila, Asuncion; Cardona, Xavier; Martin-Baranera, Montserrat; Leon, Lucia; Caballol, Nuria; Millet, Pablo; Bello, Juan
Abstract : Abstract: Depression and sleep disorders are among the most prevalent nonmotor symptoms of Parkinson disease (PD). Because agomelatine acts as a MT1 and MT2 agonist and as a 5HT2c antagonist, this study was designed to assess the efficacy of agomelatine in treating depressive symptoms in PD patients, and the potential changes both in sleep quality and motor symptoms. Depressed patients with PD were treated with agomelatine for 6 months, and they were evaluated with an array of scales. Completed nocturnal video-polysomnography was performed at baseline and week 12. The efficacy analysis population included 24 patients (12 men). The mean (SD) age was 75.2 (8.3) years. The mean (SD) daily dose of agomelatine was 25.00 (10.43) mg at 24 weeks. No changes in dopamine replacement therapy were made. There was a significant decrease in the 17-item Hamilton Depression Scale score over the course of the study ( P < 0.0005). The Scales for Outcomes in Parkinson disease Sleep Questionnaire showed a statistically significant improvement over time in each of its subscales: nighttime sleep ( P < 0.005), last month nighttime sleep ( P < 0.0005), and daytime sleepiness ( P < 0.0005). Surprisingly, changes over time in the motor subscale of Unified Parkinson Disease Rating Scale were statistically significant ( P < 0.0005). Periodic limb movements and awakenings measured by polysomnography improved significantly ( P < 0.005 and P < 0.05, respectively). We concluded that the use of agomelatine in PD depressed patients may have a considerable therapeutic potential because of its dual action for treating both symptoms of depression and disturbed sleep given its secondary beneficial effects regarding the reduction of extrapyramidal symptoms.